Financial Performance of Micro, Small and Medium Enterprises: A Study of Deli Serdang Regency - Nur Aini; Debbi Chyntia Ovami (International Journal of Economics Development Research (IJEDR), 2023)
The purpose of this research is to examine the effect of implementation financial accounting standarts for small and medium micro entites (SAK-EMKM), human resource competencies and marketing strategy on the financial performance of MSMes in Kab. Deli Serdang. The method used in this research is quanritative. Deep sample in this study, MSME actors were registered with the Cooperative Service and MSMEs Kab. Deli Serdang with sampling technique using purposive sampling method using six criteria thenobtained the sample that met the criteria was 78 SMEs.While technique data collection in this study using a questionnaire consisting of several questions in writing posed to respondents and techniques the analysis used in this study using linear regression analysis multiplied by using the Statistical Package For Sosial Science (SPSS). Based on the results of the T test in this study, it shows that the application of SAK-EMKM has a positive and significant effect on the financial performance of MSMes, Human resource competency positive an significant effect on the financial performace of Smes, as well as marketing strategies have a positive and significant effect on MSME financial performance.Result simultaneously with the F test in this study shows that the application of SAK-EMKM, human resource competencies and strategies marketing has a positive and significant effect on the financial performanceof MSMEs Kab. Deli Serdang.